A realtime IoT-mobile-based system for mapping and monitoring water reservoirs of PDAM in Fakfak City - Arridha, Riyadh; Roy, Andi; Saputra, Muhammad Faisal; Yusril (Jurnal Mandiri IT, 2025)
The Regional Drinking Water Company (PDAM) of Fakfak plays a vital role in delivering clean water to the community. However, the current manual approach to monitoring water availability and quality in reservoirs can lead to delays in decision-making related to water distribution. This research aims to design and develop a mobile application integrated with a real-time reservoir mapping and monitoring system, utilizing Internet of Things (IoT) technology. The system employs ultrasonic sensors to measure water levels, pH sensors to assess water quality, and a microcontroller with a communication module to transmit data to a server. This data is then visualized on an Android-based application supported by integrated mapping features. The study follows a Research and Development (R&D) methodology using a prototyping model. The resulting prototype demonstrates the system’s ability to provide accurate and real-time insights on water reservoir conditions, thereby enhancing PDAM's capacity for efficient and responsive water distribution planning.